Business Plan and Customer Satisfaction: The Effect of RATER as a Mediator in the Tabalong Retail Industry - Ahmad Farhani; Rahmi Hayati (Citakonsultindo, 2025)
This research analyzes the influence of business plans on customer satisfaction with RATER dimensions as mediating variables in the retail industry of Tabalong Regency. A systematic literature review methodology was employed to synthesize relevant literature from 2019-2025 across various accredited academic databases. Findings demonstrate that business plans significantly influence RATER dimensions implementation, with reliability and responsiveness showing highest effectiveness in local retail contexts. Mediation mechanisms confirm that service quality functions as a translator converting strategic intentions into customer outcomes. Reliability and responsiveness dimensions exhibit most consistent influence on customer satisfaction, while empathy requires contextual adaptation. Theoretical contribution lies in empirical validation that business planning requires intermediate mechanisms for optimal impact creation. Practical implications indicate that retail businesses in emerging markets should prioritize investments in reliability and responsiveness dimensions as competitive advantage foundations. This research enriches understanding of mediating relationship complexity within retail ecosystems and provides strategic frameworks for customer satisfaction optimization through targeted service quality improvements in Indonesian emerging market contexts. The study contributes valuable insights for retail management theory and practice in developing economies.